An urban, water-borne outbreak of diarrhoea and shigellosis in a district town in eastern India - Saha, T; Murhekar, M; Hutin, Y J; Ramamurthy, T (The National medical journal of India, 2009)
In September 2007, the Gayeshpur municipality reported a cluster of cases with diarrhoea. We aimed to identify the causative agent and the source of the disease. We defined a case as the occurrence of diarrhoea (> 3 loose stools/day) with fever or bloody stools in a resident of Gayeshpur in September-October 2007. We asked healthcare facilities to report cases, collected stool specimens from patients, constructed an epidemic curve, drew a map and calculated the incidence by age and sex. We also conducted a matched case-control study (58 in each group), calculated matched odds ratio (MOR) and population attributable fraction (PAF), as well as assessed the environment. We identified 461 cases (attack rate: 46/1000 population) and isolated Shigella flexneri (serotype 2a and 3a) from 3 of 4 stool specimens. The attack rate was higher among females (52/1000) and those in the age group of 45-59 years (71/1000). The outbreak started on 22 September, peaked multiple times and subsided on 12 October 2007. Cases were clustered distal to a leaking pipeline that crossed an open drain to intermittently supply non-chlorinated water to taps. The 58 cases and 58 controls were matched for age and sex. Drinking tap water (MOR: 10; 95% CI: 3-32; PAF: 89%), washing utensils in tap water (MOR: 3.7; 95% CI: 1.2-11.3) and bathing in tap water (MOR: 3.5; 95% CI: 1.1-11) were associated with the illness. This outbreak of diarrhoea and Shigella flexneri dysentery was caused by contamination of tap water and subsided following repair of the pipeline. We recommended regular chlorination of the water and maintenance of pipelines.